(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information on determining the amount of organic carbon in soil using a new modern method and comparing it with the amount of organic carbon in soil in other regions. In Uzbekistan, it is possible to determine the amount of organic carbon and collect data on the amount of organic carbon in the regions.